Bioinformatics for Diagnosis, Prognosis and Treatment of Complex Diseases - Shen, Bairong; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
The book introduces the bioinformatics tools, databases and strategies for the translational research, focuses on the biomarker discovery based on integrative data analysis and systems biological network reconstruction. With the coming of personal genomics era, the biomedical data will be accumulated fast and then it will become reality for the personalized and accurate diagnosis, prognosis and treatment of complex diseases. The book covers both state of the art of bioinformatics methodologies and the examples for the identification of simple or network biomarkers. In addition, bioinformatics software tools and scripts are provided to the practical application in the study of complex diseases. The present state, the future challenges and perspectives were discussed. The book is written for biologists, biomedical informatics scientists and clinicians, etc. Dr. Bairong Shen is Professor and Director of Center for Systems Biology, Soochow University; he is also Director of Taicang Center for Translational Bioinformatics.
Bioinformatics for complex diseases: the basics -- Network based diagnosis of complex diseases -- Applications in Detection and Treatment of Complex Diseases.
Keywords: Life sciences; Oncology; Medicine; Bioinformatics; Biology -- Data processing; Life Sciences; Bioinformatics; Molecular Medicine; Cancer Research; Computer Appl. in Life Sciences